USM-KLE STUDENTS JOIN MALAYSIAN COMMUNITY IN INDIA TO MEET PRIME MINISTER - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 1 April 2017 – Some 28 USM-KLE students took part in the Malaysian Students and Community get-together session in Chennai, India to meet the Malaysian Prime Minister, Dato' Seri Najib Tun Abdul Razak. The programme was held in conjunction with the Prime Minister's visit to India, from 30th March to 4th April to meet the Prime Minister of India, Narendra Modi.